2011
DOI: 10.1186/1471-2458-11-583
|View full text |Cite
|
Sign up to set email alerts
|

A systematic examination of the use of Online social networking sites for sexual health promotion

Abstract: BackgroundIn recent years social networking sites (SNSs) have grown rapidly in popularity. The popularity of these sites, along with their interactive functions, offer a novel environment in which to deliver health promotion messages. The aim of this paper is to examine the extent to which SNSs are currently being used for sexual health promotion and describe the breadth of these activities.MethodsWe conducted a systematic search of published scientific literature, electronic sources (general and scientific se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 36 publications
2
127
0
8
Order By: Relevance
“…Information compatibility means the compatibility of patients' medical information between hospitals. A high level of information compatibility would attract more patients to visit for their follow-up treatments [30,31]. The above analysis allows us to propose the following assumption:…”
Section: Hospital Conveniencementioning
confidence: 99%
See 1 more Smart Citation
“…Information compatibility means the compatibility of patients' medical information between hospitals. A high level of information compatibility would attract more patients to visit for their follow-up treatments [30,31]. The above analysis allows us to propose the following assumption:…”
Section: Hospital Conveniencementioning
confidence: 99%
“…Medical expenditure is an important factor for patients when choosing a hospital [31]. Reducing the cost of medical services attracts significantly more patients [32].…”
Section: Medical Costsmentioning
confidence: 99%
“…As is increasingly recognised, online SNSs offer great potential for public health professionals to reach out and engage with the community at large for several reasons [1,2]. Firstly, in countries with extensive internet access, SNS use is often widespread and growing in popularity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, public health institutes and professionals have utilised SNSs for various purposes including health promotion and information distribution, intervention delivery, decreasing attrition in longitudinal studies, and study recruitment through advertisements placed on SNSs [1,2,[9][10][11][12][13][14]. However, the methods with which to use these sites most effectively to engage with the public are not yet well understood and the ways in which public health institutes are employing SNSs in their daily work are under-reported in the scientific literature [1,2,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Other people have proposed, with little retrospective evidence, the potential value of social media in public emergencies and crisis management, and how pharmacists could utilize the media in these situations. 25 In a systematic review of the use of social networking sites for promotion of sexual health, Gold et al 26 found that Facebook was the most commonly used (used for 71% of all health promotion activities identified), followed by MySpace and Twitter. These authors concluded that social networking sites have been used mainly in developed countries, including the USA and UK, to promote health-related information to young people, but note that the vast majority of health promotion projects remain unreported in the literature.…”
mentioning
confidence: 99%